2014
DOI: 10.1111/ajpy.12050
|View full text |Cite
|
Sign up to set email alerts
|

Is emotion regulation the process underlying the relationship between low mindfulness and psychosocial distress?

Abstract: Emotion regulation deficits are implicated in many forms of psychosocial distress. The aim of the present research was to investigate whether emotion regulation was the process underlying the well-established association between low dispositional mindfulness and greater psychosocial distress. Two studies are presented that examined whether non-acceptance of emotion and limited access to emotion regulation strategies were the processes underlying the association between low mindfulness and depression, anxiety, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 48 publications
1
20
0
1
Order By: Relevance
“…The results confirmed previous studies indicating association between the key variables (Goodall, et al, 2012;Pepping, et al, 2014;Siegel, 2007). Further, the analysis revealed that a sequential relationship between mindfulness and emotional regulation fully mediated the relationship between three of the identified attachment styles: secure, preoccupied and dismissive.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results confirmed previous studies indicating association between the key variables (Goodall, et al, 2012;Pepping, et al, 2014;Siegel, 2007). Further, the analysis revealed that a sequential relationship between mindfulness and emotional regulation fully mediated the relationship between three of the identified attachment styles: secure, preoccupied and dismissive.…”
Section: Discussionsupporting
confidence: 92%
“…The Non acceptance and Awareness factors of the DERS, which appear to share similarity with the FFMQ were removed and the mediation analysis conducted again (Pepping, et al, 2014). The pattern of results remained unchanged indicating both variables contributed to the sequential mediational model.…”
Section: Resultsmentioning
confidence: 99%
“…High dispositional mindfulness is also associated with romantic relationship satisfaction (Barnes, Brown, Krusemark, Campbell, & Rogge, 2007;Wachs & Cordova, 2007), initial romantic attraction in women (Janz, Pepping, & Halford, 2015) and satisfaction with interpersonal relationships (Pepping, O'Donovan, Zimmer-Gembeck, & Hanisch, 2014). In brief, individuals higher in dispositional mindfulness fare better than their less mindful counterparts on a wide range of psychological and social outcomes.…”
Section: Individual Differences In Dispositional Mindfulnessmentioning
confidence: 99%
“…The wide uptake of mindfulness-based interventions in clinical settings (Baer, Smith, & Allen, 2004) has been followed by organisational practitioners advertising the benefits of mindfulness to employees and leaders (Hafenbrack, 2017). Additionally, there is a need to explore the mechanisms that explain how mindfulness leads to outcomes; this study will contribute to the evidence for emotion regulation as one such mechanism (Pepping, O'Donovan, Zimmer-Gembeck, & Hanisch, 2014). The aim of this study is to extend the empirical evidence base for mindfulness in the workplace by investigating the role of mindfulness and interpersonal relationships, specifically in co-worker relationships.…”
Section: Introductionmentioning
confidence: 99%